Peran Kepemimpinan Demokrasi Kepala Sekolah dalam Meningkatkan Efektivitas Kerja Guru SMP - Dwi Aprillia Setia Asih; Kodariyah Kodariyah; Henny Suharyati (Badan Penerbit STIEPARI Press, 2025)
This resealrch alims to alnallyze the role of democraltic lealdership of school principalls in enhalncing tealchers' work effectiveness alnd to identify the challlenges falced by school principalls in improving tealchers' work effectiveness alt SMP Negeri 2 Balndalr Maltalralm. Through al quallitaltive descriptive alpproalch with al calse study, daltal wals collected through interviews, observaltions, alnd documentaltion from the principall, tealchers, alnd educaltionall stalff. The results indicalte thalt the democraltic lealdership alpplied by the principall significalntly impalcts tealchers' motivaltion, collalboraltion, alnd performalnce. Tealchers feel more vallued becaluse they alre involved in decision-malking, given opportunities to develop themselves through relevalnt tralining, alnd receive recognition for their alchievements. This lealdership allso enhalnces collalboraltion almong tealchers alnd hals al positive impalct on improved tealcher performalnce, als evidenced by al high tealcher alttendalnce ralte (95%) alnd al job saltisfalction level (80%). Furthermore, motivaltion alnd collalboraltion halve increalsed, with 90% of tealchers feeling more motivalted alfter receiving alwalrds, alnd this hals al positive impalct on student lealrning outcomes, which halve improved by 15% over the palst two yealrs. However, the study allso identified constralints in the limitaltions of school falcilities, such als clalssrooms, libralries, alnd lalboraltories thalt alre still inaldequalte. These findings emphalsize the importalnce of the principall's role in implementing inclusive alnd palrticipaltory lealdership to crealte al productive working environment thalt supports the improvement of educaltion quallity.